Conocimientos y prácticas sobre prevención del dengue, en los estudiantes del primer a tercer Año de Bachillerato, del Colegio Nacional Zapotillo. - Sánchez Rogel, Mariuxi Cecibel (2017)
In the present investigation an epidemiological descriptive study and cross-section, in which knowledge and practices about dengue prevention in students from first to third year of high school the Zapotillo National College were reflected during the period January was held - July 2016, data were obtained through a survey that students of the school the same who met the criteria for inclusion and exclusion was applied, with the following results: in epidemiological variables 56% of students from sex male, 53% are between 16 and 17 years and 68.5% belong to the urban sector; with regard to knowledge about this disease the 54.71% have a good knowledge about dengue; 45.29% are regularly the knowledge about this disease. With regard to the 48.98% practices takes appropriate measures to prevent dengue pathology practices, ie remove accumulated water, hatcheries, clean the house, throw the trash and unused objects; while 51.02% are inadequate to prevent dengue practices. Keywords: dengue, knowledge, practices